FoMC69 Gene in Fusarium oxysporum f. sp. radicis-lycopersici Is Essential for Pathogenicity by Involving Normal Function of Chlamydospores - Kazunori Sasaki; Yumi Ito; Yuki Hamada; Ayano Dowaki; Sudisha Jogaiah; Shin-ichi Ito (Pathogens, 2022)
Fusarium oxysporum f. sp. radicis-lycopersici (Forl) causes crown and root rot disease in tomato, effecting severe economic losses. However, research on the pathogenicity genes and infection strategy of Forl is limited compared to that on F. oxysporum f. sp. lycopersici (Fol). In this study, we characterized FoMC69 gene in Forl as a homolog of MC69 required for pathogenicity in rice blast pathogen—Magnaporthe oryzae. Gene expression analysis revealed that FoMC69 expressionin Forl is higher than that in Folin planta. FoMC69-knockout mutant of Forl had significantly reduced root rot symptoms compared to the wild-type strain, and full pathogenicity was restored by complementation. By contrast, ΔFoMC69 mutant of Fol presented the same symptoms as the wild type, suggesting that FoMC69 of Forl, but not of Fol, was essential for full virulence in tomato plants. Morphological differences between the Forl and ΔFoMC69 in the roots were observed by fluorescent labeling using WGA-FITC. Chlamydospores of the ΔFoMC69 mutant of Forlcontinuously increased during infection and were three times higher than that of the wild type at 21 days post-inoculation. These observations suggest that FoMC69 of Forl is required for virulence to tomato plants by involving the normal development and germination of chlamydospores.